INTEGRATING TECHNOLOGY IN ISLAMIC RELIGIOUS EDUCATION: EVALUATING THE EFFECTIVENESS OF E-LEARNING PLATFORMS IN ENHANCING STUDENT ENGAGEMENT AND UNDERSTANDING - Saepudin, Aep (GoAcademica Research dan Publishing, 2022)
Technology integration in Islamic religious education is becoming increasingly important in today's digital era. Challenges in conventional education, such as limited access in remote areas and inequality in the quality of education, have been exacerbated by the impact of the COVID-19 pandemic. Therefore, technology offers a great opportunity to expand access and improve the quality of education through e-learning platforms. This study aims to evaluate the effectiveness of e-learning platforms in increasing student engagement and understanding in Islamic religious education. This study uses a qualitative approach by collecting data from various relevant sources, including previous research and studies. The collected data are then processed systematically to find main patterns and themes. The results show that e-learning can increase student engagement through interactive and multimedia features, as well as improve understanding of subject matter with the use of multimedia that enriches the learning experience. However, technical challenges such as internet access and limited devices, as well as pedagogical challenges such as adaptation of teaching methods and teacher training, need to be overcome. Adequate support for teachers and students, as well as an approach that is sensitive to traditional values, are key to the successful implementation of e-learning. With the right strategy, e-learning can be an effective tool for creating a knowledgeable and noble generation in Islamic religious education.